KNOWLEDGE AND PRACTICE TOWARDS COSMETICS AND THEIR ADVERSE REACTIONS AMONG UNDERGRADUATE MEDICAL, PHARMACY, AND PHYSIOTHERAPY STUDENTS - K, GIRISH; K, VASUNDARA; R, JYOTHI; ARUNNAIR, VIJAYAMATHY (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objectives: The objectives of the study were to evaluate the knowledge, practice, and pattern of cosmetic use and their adverse reactions amongst medical, pharmacy, and physiotherapy undergraduates. Methods: This was a cross-sectional, questionnaire-based study conducted among 202 2nd-year medical (113), Pharmacy (51), and Physiotherapy (38) students of KIMS, Bangalore, India for a period of 1 month. Results obtained were analyzed using descriptive statistics. Results: About 75.2% of students were aware of cosmetics and their adverse reactions, still 36.7% of students will continue using them because they were convinced about them. Pharmacy students had less knowledge of the animal, alternate testing, and preventive measures compared to medical and physiotherapy students. Overall n=71, (35.1%) of students had adverse reactions from cosmetic usage, the most common product being fairness cream and the adverse reactions include itching, acne, and rashes. Conclusion: Overall, the undergraduate medical, pharmacy, and physiotherapy students had good insight and practice toward cosmetics and their adverse reactions, nevertheless the awareness of pharmacy students was comparatively less than medical and physiotherapy students. Hence, educational intervention on the effective, safe, and proper use of cosmetics in the future needs to be implemented especially among pharmacy students.